'Greece will decide the future of Europe': The recontextualisation of the Greek national elections in a British broadsheet newspaper. (July 2014) - Lampropoulou, Sofia
This article explores the representation of the Greek national elections in a British broadsheet newspaper and their recontextualisation through the prism of crisis. I focus on speech representation as a recontextualisation device that serves as a bridge between speech production and text consumption. Specifically, the paper addresses the discursive framing of the crisis by focusing on the 'speakers', namely the social actors who are represented as speaking, the actions in which they are involved and the power role relationships established between them. I argue that a polarised image of crisis is constructed and that the framing of the Greek elections in this particular broadsheet results in double-voicing that positions Greece as either dependent on or independent of Europe. This double-voicing seems to contribute to the maintenance of domination and social control and helps sustain dominant discourses circulating in the broader socio-cultural context.